Examination of the relationship between generating examples and checking examples in children (Journal of Basic and Applied Research in Biomedicine, 2022)
Examples play an important role in teaching mathematics. Thus, the present research aims at study of the relationship between examples and understanding mathematics. To do so, the following questions are raised: when generating and checking examples, one aspects is given attention or different aspects? Does the learner’s ability in generating more examples make the learner not to check the examples?. To collect the data, the subjects were interviewed with all elementary students in grade three, four and five. were selected that through interview and tracking students’ intellectual method via frequent questions and controlling their drafts, their generated examples become identified. It should be mentioned names are unreal. The results show that there are differences between “generating example” and “checking examples”. Also, it looks that a strong relationship is available between generating example for a concept and understanding that concept.